CARE MANAGEMENT DURING ADVANCED AIRWAY SUPPORT IN PREHOSPITAL CARE: A DECISION-MAKING ALGORITHM. - Faria, Welliton Pestana; Moreira, Ana Paula Amorim; Nassar, Pedro Ruiz Barbosa; Christovam, Bárbara Pompeu; Paes, Graciele Oroski; de Assis, Allan Peixoto (Texto & Contexto Enfermagem, 2025)
Objective: to develop a care management algorithm for upper airway management with laryngeal masks by nurses working in prehospital care services. Method: a multi-method implementation improvement study conducted in prehospital care services administered by the Rio de Janeiro State Health Department. The study was organized in two stages. A literature review was conducted in the pre-implementation stage to identify the best scientific evidence related to advanced airway support. The participants completed an instrument in the implementation stage on care management for upper airways with laryngeal masks. Data were analyzed using SPSS 22.0 software. The distribution of quantitative variables was summarized into proportions of interest: mean, median, minimum, maximum, and standard deviation. Finally, the algorithm was evaluated by expert nurses through a workshop using the brainstorming technique. Results: the majority of professionals were female (63.9%), with 16.8 years of training and more than 10 years of experience in prehospital care (80.6%). As a result of the study, two mind maps were created presenting the evidence selected for structuring the algorithm's decision-making inputs, stratifying the data into a finite sequence of care instructions focused on upper airway management. Conclusion: the proposed improvement implementation considers using the algorithm as a strategy for systematizing differentiated and optimal nursing care, capable of appropriately prioritizing care.